Pengaruh Bahan Perendaman Pada Tahap Ekstraksi Terhadap Mutu Benih Melon (Cucumis melo L.) Varietas Green Flash - Azizah Khoirul Inayah; Budi Wijayanto; Ananti Yekti (Universitas Sebelas Maret, 2025)
Quality seeds are seeds that have high quality. One ofthemethods for seed processing is to use the rapid extraction method. In this method, extraction is used for the separation of seeds with their mucus. The final project research aims to determined the soaking material at the seed extraction stage quickly and precisely to remove mucus in seeds that inhibit seed germination on physiological quality. This study was held in March to May 2023 at CV Multi Global Agrindo, Karanganyar and at the Polbangtan Yogyakarta Seed Technology Laboratory andusingRandomized Complete Design (RCD). Factor I in the form of extraction soaking material (E) were control, HCl 2%, Quicklime, 24-hour Fermentation, and Detergent. Exist 5 treatments with 4 repetitions each. The parameters were germination, coarseness, vigor index, and maximum growth potential. The statistical data were analyzed using ANOVA. The results of this study showed that the treatment of soaking material at the extraction stage was the best by producing quality melon seeds, namely soaking extraction material with 2% HCl for 2 hours was able to remove melon sarcotesta that inhibited germination, indicated by the parameters of vigor index, germination, coarseness of growth and maximum growth potential that differed very real.